2018
DOI: 10.1002/adma.201801198
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Diselenide‐Bridged Mesoporous Silica Nanoparticles for Dual‐Responsive Protein Delivery

Abstract: Controlled delivery of protein therapeutics remains a challenge. Here, the inclusion of diselenide-bond-containing organosilica moieties into the framework of silica to fabricate biodegradable mesoporous silica nanoparticles (MSNs) with oxidative and redox dual-responsiveness is reported. These diselenide-bridged MSNs can encapsulate cytotoxic RNase A into the 8-10 nm internal pores via electrostatic interaction and release the payload via a matrix-degradation controlled mechanism upon exposure to oxidative or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
205
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(206 citation statements)
references
References 53 publications
0
205
0
1
Order By: Relevance
“…[61] Gram-negative bacterial membranes would be replaced by secreted outer membrane vesicles (OMVs) because it difficult to extract bacterial membranes due to the peptidoglycan proteins of cell walls. [64] The cell membrane fragments would then be washed, purified, and extruded following the steps mentioned above. The extraction of membranes from cancer cells, leukocytes, and stem cells is more complicated than the extraction from nucleus-free cells.…”
Section: Strategies To Prepare Cell Membrane-based Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Gram-negative bacterial membranes would be replaced by secreted outer membrane vesicles (OMVs) because it difficult to extract bacterial membranes due to the peptidoglycan proteins of cell walls. [64] The cell membrane fragments would then be washed, purified, and extruded following the steps mentioned above. The extraction of membranes from cancer cells, leukocytes, and stem cells is more complicated than the extraction from nucleus-free cells.…”
Section: Strategies To Prepare Cell Membrane-based Vesiclesmentioning
confidence: 99%
“…[64] We will summarize recent studies on the application of inflammatory-related cell homing and targeting to tumor sites for cancer therapy. The sustained presence of inflammatory mediators maintains the advantage of an environment suited for tumor cell proliferation.…”
Section: Tumor Inflammatory Microenvironmentmentioning
confidence: 99%
“…After it cures the cancer in vivo, the nanoparticle can be degraded to small molecules or triggered to small pieces by tumor environment (Yue et al, ). Recently, a new generation of degradable organosilica nanoparticles was developed for bio‐macromolecules delivery (Shao et al, ). The silica nanoparticles were diselenide‐bridged and can be biodegraded by GSH and ROS in tumor tissues.…”
Section: Dual and Multi‐responsive Nanomedicinementioning
confidence: 99%
“…This redox potential difference also favors the development of artificial redox‐responsive delivery systems. Nanovectors have been manufactured that are stable in the extracellular environment, whereas they are unstable in the intracellular environment because high levels of GSH in cancer cells promote the degradation of chemical linkages of disulfide and diselenide bonds in the carriers to release genes …”
Section: Dynamic and Bioresponsive Processes Have Inspired Designs Inmentioning
confidence: 99%
“…Nanovectors have been manufactured that are stable in the extracellular environment, whereas they are unstable in the intracellular environment because high levels of GSH in cancer cells promote the degradation of chemical linkages of disulfide and diselenide bonds in the carriers to release genes. 12,[34][35][36][37] Recognizing the advantages of disulfide bonds for controlling gene packing and release, Klein et al 38 reported bioreducible sequence-defined lipo-oligomers for siRNA delivery, which precisely positioned disulfide linkages between the fatty acid and polycationic domain via a Fmoc-succinoyl-cystamine building block. The designed carriers with disulfide bonds not only showed high gene silencing efficacy, but also low cytotoxicity compared to their non-reducible lipooligomer analogs.…”
Section: Redox-responsive Delivery Systemsmentioning
confidence: 99%